1989
DOI: 10.1021/bi00435a001
|View full text |Cite
|
Sign up to set email alerts
|

How do serine proteases really work?

Abstract: Recent advances in genetic engineering have led to a growing acceptance of the fact that enzymes work like other catalysts by reducing the activation barriers of the corresponding reactions. However, the key question about the action of enzymes is not related to the fact that they stabilize transition states but to the question to how they accomplish this task. This work considers the catalytic reaction of serine proteases and demonstrates how one can use a combination of calculations and experimental informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
373
0
5

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(412 citation statements)
references
References 51 publications
(80 reference statements)
31
373
0
5
Order By: Relevance
“…It has been suggested that the binding of substrates or structurally related inhibitors will induce a conformational change resulting in steric compression between histidine-57 and aspartate-102 and the formation of a low barrier hydrogen bond raising the pK a of histidine-57 [37,38]. Recent calculations [39,40] support the proposal [15,41] that inhibitor or substrate binding causes desolvation of the active site histidine residue in the serine proteases raising the pK a of the histidine residue and allowing it to be an effective general base catalyst enhancing the nucleophilicity of the hydroxyl group of serine-195 [15,21,33,41]. Raising the histidine pKa also allows it to act as a general acid catalyst for the breakdown of the tetrahedral intermediate [13-15, 21, 42] and to stabilize oxyanion formation [15,21].…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that the binding of substrates or structurally related inhibitors will induce a conformational change resulting in steric compression between histidine-57 and aspartate-102 and the formation of a low barrier hydrogen bond raising the pK a of histidine-57 [37,38]. Recent calculations [39,40] support the proposal [15,41] that inhibitor or substrate binding causes desolvation of the active site histidine residue in the serine proteases raising the pK a of the histidine residue and allowing it to be an effective general base catalyst enhancing the nucleophilicity of the hydroxyl group of serine-195 [15,21,33,41]. Raising the histidine pKa also allows it to act as a general acid catalyst for the breakdown of the tetrahedral intermediate [13-15, 21, 42] and to stabilize oxyanion formation [15,21].…”
Section: Discussionmentioning
confidence: 94%
“…of chymotrypsin-like proteases is not accessible to the solvent and forms an H-bond with Asplo2, thus making an important contribution to its topology ( Fig. 5 ; Warshel et al, 1989). In both molecules of factor D, the hydroxyl group of Thr2I4 is pointed away from Asp'", failing to affect its orientation (Fig.…”
Section: Catalytic Triadmentioning
confidence: 99%
“…petent configuration in the active site (Warshel et al, 1989). Likewise, it is possible that a bound metal cation in the vicinity of His-57 could destabilize the positive charge developed on this amino acid residue in the transition state.…”
Section: Jomentioning
confidence: 99%